Hubungan persepsi sosial siswa berkebutuhan khusus dengan bullying di sekolah inklusi - Reza Arifni; Firman Firman (Universitas Negeri Padang, 2023)
Bullying is a hurtful behavior carried out repeatedly by a strong party against a weak party, the aim is to control and provide physical and verbal assault treatment, so that later it will cause physical and psychological pain. one of the factors that influence bullying is perception. students who have negative social perceptions of students with special needs will carry out acts of bullying. This study uses a quantitative method with a descriptive correlational approach. the population in the study amounted to 536 students of SMP 5 Padang who perceived students with special needs negatively so that they carried out acts of bullying against students with special needs using a stratified random sampling technique. data collection using product moment correlation formula. the results of this study found: 1. social perceptions of students with special needs are in the medium category with a percentage of 47.82%, 2. bullying is in a very low category with a percentage of 32.17%, 3. there is a negative and significant relationship between social perceptions of students with special needs with bullying, with rho=-0.233 and a significance level of 0.000